Living the Good Life in a Non-Growth World. Investigating the Role of Hierarchy - Blair Fix (Forum on Capital As Power - Toward a New Cosmology of Capitalism, 2021)
Humanity's most pressing need is to learn how to live within our planet's boundaries - something that likely means doing without economic growth. How, then, can we create a non-growth society that is both just and equitable? I attempt to address this question by looking at an aspect of sustainability (and equity) that is not often discussed: the growth of hierarchy. As societies consume more energy, they tend to become more hierarchical. At the same time, the growth of hierarchy also seems to be a key driver of income/resource inequality. In this essay, I review the evidence for the joint relation between energy, hierarchy and inequality. I then speculate about what it implies for achieving a sustainable and equitable future. NOTE: This essay was written for and supported by the Seoul Platform for Initiating Discourses on an Equitable and Resilient Society.
Keywords: P16; Q4; D3; 330; hierarchy; energy; inequality; power; sustainability; wellbeing